1990
DOI: 10.1002/j.1460-2075.1990.tb07370.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel transposition system in Drosophila melanogaster depending on the Stalker mobile genetic element.

Abstract: Crosses between the Drosophila melanogaster y2sc1waG strain or some of its derivatives and the FM4 strain yielded insertional mutagenesis with a frequency of 10(‐3)‐10(‐4). The system differs in several respects from the known cases of hybrid dysgenesis: (i) it does not depend on the direction of a cross; (ii) destabilization continues for a long time after initial crosses; (iii) mutations may occur at different stages of development. The mutation in the yellow locus has been cloned and found to depend on inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 9 publications
(6 reference statements)
3
21
0
Order By: Relevance
“…In D. virilis, four different TEs (Ulysses, Penelope, Paris and Helena) have been mobilized by an hybrid dysgenesis process (Petrov et al, 1995), which have been demonstrated to be associated to the Penelope TE by a mechanism in which mobilization of a single element triggers that of others, perhaps through chromosome breakage or for the supply of the proteins necessary for transposition (Evgen'ev et al, 1997) Not all TE mobilizations are the consequence of dysgenic crosses; other crosses can also induce transpositions in Drosophila. In D. melanogaster, the stalker element has been mobilized after crosses between two different mutant strains (Georgiev et al, 1990). Changes in the chromosomal insertion pattern of the copia element have been observed during the process of making chromosomes homozygous by the use of balancer chromosomes (García Guerreiro and Biémont, 1995).…”
Section: Genomic Stressesmentioning
confidence: 99%
“…In D. virilis, four different TEs (Ulysses, Penelope, Paris and Helena) have been mobilized by an hybrid dysgenesis process (Petrov et al, 1995), which have been demonstrated to be associated to the Penelope TE by a mechanism in which mobilization of a single element triggers that of others, perhaps through chromosome breakage or for the supply of the proteins necessary for transposition (Evgen'ev et al, 1997) Not all TE mobilizations are the consequence of dysgenic crosses; other crosses can also induce transpositions in Drosophila. In D. melanogaster, the stalker element has been mobilized after crosses between two different mutant strains (Georgiev et al, 1990). Changes in the chromosomal insertion pattern of the copia element have been observed during the process of making chromosomes homozygous by the use of balancer chromosomes (García Guerreiro and Biémont, 1995).…”
Section: Genomic Stressesmentioning
confidence: 99%
“…Drosophila e(y)1 was initially phenotypically characterized by enhancing the phenotype of the y 2 allele when mutated (Georgiev et al, 1990). A following study demonstrated that e(y)1 is highly expressed in follicle cells and oocytes during Drosophila oogenesis and that decreased e(y)1 transcription causes dramatic underdevelopment of the ovaries and sterility of female flies (Soldatov et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that all components of the TFIID complex we tested, except TAF12, are required for Notch signaling, at least during Drosophila wing development. The e(y)1, e(y)2 and e(y)3 genes were genetically identified as the respective mutations enhance the phenotype of the y 2 mutation (Georgiev and Gerasimova, 1989;Georgiev et al, 1990), but only E(y)1 is believed to be a component of the TFIID complex. To investigate whether e(y)2 or e(y)3 plays a similar role in Notch signaling as that of e(y)1, we compromised e(y)2 function by expression of e(y)2-RNAi and found that it was not required for Notch activity during wing development (Fig.…”
Section: /+mentioning
confidence: 99%
“…Indeed the P/M, hR and hobo hybrid dysgenesis systems in D. melanogaster are capable of activating transposable elements, inducing sterility, gonadal atrophy and of increasing the mutation rate in F1 progeny of intraspecific crosses between males from a natural population and females from a long established laboratory strain. Retrotransposons can also be mobilized after crosses involving laboratory or wild lines and some balancer stocks as observed in Pasyukova et al (1988), Georgiev et at. (1990), Pasyukova & Nuzhdin (1993) and Garcia Guerreiro & Biémont (1995).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, somatically active transposable elements have been identified in D. melanogaster (Blackman & Gelbart, 1989;Georgiev et a!., 1990;Kim & Belyaeva, 1991a,b), D. mauritiana (Hart!, 1989), Caenorhabditis elegans (Emmons & Yesner, 1984;Moermann & Waterson, 1989), Zea mays (Federoff, 1989), Antirrhinum majus (Coen et al, 1989) and mice (Seperack et al, 1988).…”
Section: Introductionmentioning
confidence: 99%